Model Pelayanan Berdasarkan Indeks Kepuasan Masyarakat pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Seram Barat - Julis Nahuway; Hendry Selanno; Mike J Rolobessy (MAN 4 Kota Pekanbaru, 2025)
This study aims to analyze and formulate a service model based on the Community Satisfaction Index (IKM) at the Population and Civil Registration Office of West Seram Regency. The research uses a descriptive quantitative method with a Likert scale and analyzes data based on the 14 IKM elements established in the Regulation of the Ministry of Administrative and Bureaucratic Reform. A total of 129 service users participated as respondents. Data were processed using descriptive statistics and spider web analysis. The results concluded that the IKM scores ranged from 3.59 to 3.84, placing the overall average IKM of 3.72 in the “Good” category. The recommended service model emphasizes maintaining high service standards through fast, responsive, fair, friendly, and transparent procedures. Officer discipline, ability, and assertiveness must be strengthened alongside clear service costs and schedules. Improving comfort and integrating digital service features are also essential to enhance efficiency and public satisfaction.